Self-Efficacy Mediates The Influence Of Financial Knowledge And Financial Attitude On Financial Behavior In Wonokerto Market Traders, Bantur District, Malang Regency - Rahila Iftikhar; Muhadjir Anwar (UNIVERSITAS PAKUAN, 2024)
Financial behavior is the patterns, habits, and attitudes of individuals towards finance and the way they react to certain financial situations. This study aims to determine the influence of financial knowledge and financial attitude on financial behavior with self-efficacy as a mediating variable (a study on Wonokerto Market Traders, Bantur District, Malang Regency. The number of samples was 106 respondents with probability sampling techniques, and the method used was simple random sampling with data collection using questionnaires and analysis using PLS. The results showed that financial knowledge could not contribute to financial behavior, financial attitude contributed to financial behavior, self-efficacy as a mediating variable contributed to the influence of financial knowledge on financial behavior, and Self-efficacy as a mediating variable cannot contribute to the impact of financial attitude on financial behavior.